Transformational Leadership Practices of School Heads: Teachers’ Motivation and School Performance - Ermita, Lota; Baysa, Marilyn L (Edu Berkah Khatulistiwa, 2025)
Transformational leadership plays a critical role in shaping school effectiveness, particularly in fostering teacher motivation and improving institutional performance. This study examines the transformational leadership practices of school heads, integrating the 5C indicators—Clarity, Collaboration, Confidence-building, Coaching, and Change Management—to assess their impact on teacher motivation and school performance using a quantitative research approach. Through structured survey instruments, data were collected from school heads and teachers to analyse leadership effectiveness. Statistical methods, including descriptive and inferential analyses, were employed to determine the relationships between transformational leadership behaviours and teacher motivation, instructional quality, and school-wide performance metrics. The study focuses on how school heads establish clear objectives (Clarity), foster teamwork and shared vision (Collaboration), instil professional confidence (Confidence-building), provide mentorship and development (Coaching), and effectively manage institutional transitions (Change Management) to optimize educational outcomes. Findings indicate that transformational leadership practices rooted in the 5C framework significantly enhance teacher motivation, leading to higher job satisfaction, improved instructional delivery, and strengthened student performance. Data analysis confirms a strong positive correlation between leadership effectiveness and institutional success, reinforcing the necessity of leadership development initiatives that emphasize the 5C principles. This research contributes to the growing body of educational leadership literature by offering empirical evidence on applying transformational leadership through a structured quantitative analysis. Recommendations for policy enhancement, leadership training programs, and institutional strategies are proposed to further empower school heads in cultivating high-performing and resilient academic environments.